Corporate social responsibility and multinational enterprise identity: insights from a mining company's attempt to localise in Ghana. (3rd September 2018) - Patnaik, Swetketu; Temouri, Yama; Tuffour, James; Tarba, Shlomo; Singh, Sanjay Kumar
ABSTRACT: This paper investigates how a US gold mining multinational enterprise (MNE) – one of the world's largest – operates its subsidiaries in various parts of the world by creating a unique 'glocal identity'. The US parent company has experienced several significant challenges across its network of subsidiaries. These challenges were mostly linked to the enforcement of the MNE's identity and culture in its host environment. We contribute by describing, in detail, the attempts made by this company to localise its corporate social responsibility practices in Ghana as it sought to gain legitimacy and create an identity that would overcome the issues relating to the liability of foreignness. Our data come from a combination of sources, including questionnaires and detailed semi-structured interviews conducted with the key management employees of the mining company, members and opinion leaders of the company's host communities, and secondary sources. Our main finding is that the construction of a 'host-friendly' identity was centred around the mining company's involvement with the Newmont Ahafo Development Foundation.